Numerical investigation of trihybrid nanofluid heat transfer in a cavity with a hot baffle - Rajab Alsayegh (Case Studies in Thermal Engineering)
Trihybrid nanofluids, which combine the benefits of three distinct types of nanoparticles, have significant potential to enhance heat transfer in various thermal management applications. Understanding their behaviour in confined geometries with complex boundary conditions, such as a free surface and heated obstacle, is important to optimize their performance. This study investigates the heat transfer characteristics of a Cu-Al2O3-MWCNT-oil trihybrid nanofluid within a square cavity featuring a hot baffle and a free surface. Using numerical simulations and Patankar's blocked-off region method, a parametric study was conducted, varying the Rayleigh number (5000–50,000), nanoparticle volume fraction Φ (0–0.06), obstacle size and aspect ratio (h:w from 0.7 to 9), and Marangoni number (−10,000 to 10,000). The results reveal that negative Marangoni (Ma) numbers enhance convective heat transfer due to the synergistic interaction between the thermocapillary and buoyancy forces. Conversely, positive Marangoni numbers hinder heat transfer owing to competition between these forces. With increasing Rayleigh number (Ra), heat transfer enhancements of up to 45 %, 18 % with nanoparticle addition, and 22 % with varying obstacle sizes were observed. Therefore, these parameters can be varied to optimize the thermal design.